Fungal Community Associated with Dactylopius (Hemiptera: Coccoidea: Dactylopiidae) and Its Role in Uric Acid Metabolism - Vera-Ponce de León, Arturo; Sanchez-Flores, Alejandro; Rosenblueth, Mónica; Martínez-Romero, Esperanza (Frontiers in Microbiology, 2016)
We studied fungal species associated with the carmine cochineal Dactylopius coccus and other non-domesticated Dactylopius species using culture-dependent and -independent methods. Thirty seven fungi were isolated in various culture media from insect males and females from different developmental stages and Dactylopius species. 26S rRNA genes and ITS sequences, from cultured fungal isolates revealed different species of Cryptococcus, Rhodotorula, Debaryomyces, Trametes, and Penicillium, which are genera newly associated with Dactylopius. Uric acid (UA) and uricase activity were detected in tissues extracts from different insect developmental stages. However, accumulation of high UA levels and low uricase activities were found only after antifungal treatments, suggesting an important role of fungal species in its metabolism. Additionally, uricolytic fungal isolates were identified and characterized that presumably are involved in nitrogen recycling metabolism. After metagenomic analyses from D. coccus gut and hemolymph DNA and from two published data sets, we confirmed the presence of fungal genes involved in UA catabolism, suggesting that fungi help in the nitrogen recycling process in Dactylopius by uricolysis. All these results show the importance of fungal communities in scale insects such as Dactylopius.